PEMBANGUNAN MASYARAKAT PERKOTAAN BERKELANJUTAN PERSPEKTIF PARTISIPASI KOMUNITAS - Tampubolon, Dahlan; Kornita, Sri Endang; Afriyanni, Afriyanni (Universitas Riau, 2022)
Many city programs only provide urban infrastructure but ignore the participation and governance of local communities. Public and community participation indicates the success of the settlement of slums in residential areas. This paper aims to intensively explain and analyze the role and governance of the community in urban programs in Tuah Karya Village, Tuah Madani District, Pekanbaru City. This research involved interviews with community leaders and participants in volunteer groups and residents. This paper also uses analysis of government statistics, documents, and other materials. The self-management of the RW-RT in Tuah Karya provides valuable experience for sustainable community development, especially for self-governance communities where community governance has shifted from bureaucracy to democracy. Sustainable development in urban communities offers a possible pathway and symbol for self-organizing urban communities in the coming era. Its cost-effective institutional design contributes significantly to sustainable community development, partly solving the current failure to promote urban sustainability. Volunteer groups and active public participation help support the RT institution. The lack of volunteer groups is still an obstacle to many RTs to mobilize public participation organized by community members themselves.